Optimization of the adsorption of lead (II) by hydroxyapatite using a factorial design: Density functional theory and molecular dynamics - El Hammari, L.; Hamed, R.; Azzaoui, K.; Jodeh, S.; Latifi, S.; Saoiabi, S.; Boukra, O.; Krime, A.; Boukra, A.; Saoiabi, A.; Hammouti, B.; Khan, M. M.; et al. (Frontiers in Environmental Science, 2023)
Hydroxyapatite (HAp), synthesized through a wet chemical procedure, was employed to adsorb lead (II) from an aqueous solution. HAp was characterized using Fourier transform infrared, X-ray diffraction, Brunauer-Emmett-Teller analysis, and scanning electron microscopy. The removal of Pb+2 was investigated using the factorial design approach to investigate the efficiency of different Pb+2 concentrations, contact time of adsorption, and HAp mass. The greatest removal (98.94%) of Pb+2 was obtained at a starting concentration of 50 mg/L, a contact period of 15 minutes, and a pH of 8. At 323 K, the isothermal adoption module was fitted to the Langmuir isotherms with a regression coefficient (R2) of 0.96. The thermodynamic calculations revealed that the adsorption process was exothermic and spontaneous and predominantly dominated by chemisorption. Furthermore, the maximum adsorption capacity (Qmax) at equilibrium was 90.18 mg/g, as well the adsorption kinetics specified by a pseudo-second-order kinetic model. DFT and theoretical studies showed that the results of the experiment are correlated by the observation of a much higher negative value of Eads for the lead ion adsorbate molecules as they attached to the surface of the adsorbent.